White Matter Integrity in Individuals At-Risk for PTSD Development: a Longitudinal Investigation - (:unkn) unknown (My University, 2019)
Trauma exposure is prevalent and while most are resilient, some go on to develop post-traumatic stress disorder (PTSD)—an anxiety-related disorder that results from traumatic experience. The brain changes that result from traumatic experience and PTSD are not well understood. Further, little is known about what distinguishes those who are resilient after trauma from those at risk for developing PTSD. Previous work indicates white matter integrity may be a useful biomarker in predicting PTSD and researchers have found changes in the integrity of three white matter tracts—the cingulum bundle, corpus callosum (CC), and uncinate fasciculus (UF)—in the aftermath of trauma. However, few have examined the relationship between white matter integrity and PTSD symptoms longitudinally. Thus, the aims of the current study are 1) to investigate the predictive utility of white matter integrity in the acute stages of trauma to chronic PTSD symptoms and 2) to examine how white matter integrity varies with PTSD symptoms over time. Fifty-seven individuals being treated for traumatic injuries in the emergency department at Froedert Hospital (Milwaukee, WI) completed several self-report measures and underwent structural and diffusion-weighted magnetic resonance imaging at 2 weeks (T1) and 6 months (T2) post-trauma. At T1 greater UF integrity at T1 was related to greater T2 arousal symptoms. In addition, greater T1 anterior cingulum integrity was related to greater T2 re-experiencing symptoms. However, decreased anterior cingulum and CC integrity from T1 to T2 was related to increased symptoms over time. Therefore, acute white matter integrity post-trauma may be a useful predictor of chronic PTSD symptoms, and changes in white matter integrity may track changes in symptoms over time. Together these results suggest white matter integrity may be a potential biomarker for clinicians to help identify those at risk for PTSD development.
Keywords: DTI; PTSD; Trauma; White Matter